#TITLE_ALTERNATIVE# - ALI AFIFF (NIM 19005010), SALLY
Business Expansion is needed by a company to attain efficiency to be more competitive and also to increase a company's profit. Business Expansion could be in many ways, such as; merger, acquisition, hostile takeover, and leverage buyout. But Companies in Indonesia prefer to take Acquisition in order to expand their businesses. In Acquisition theories by Abdul Moein; said that there are three conditions in company (1) Grows and burgeons dynamically. (2) In a static condition, and (3) in a regression condition. Those points could happen through business expansion, either in internal growth or external growth. One of External growth is Acquisition to another company. This is the reason for a company to do an Acquisition. But there is a question about this thing. Does the company that conduct the acquisitions have a good performance and gives a financial advance? It is an interesting topic to learn and see, if a new company that conduct the acquisition have a good performance compared to the condition before the acquisition or not. If the company's financial performance that conducted the acquisition is raised, then we can say that it has a good performance. There were 155 companies that did an acquisition in years of 1995-2005. But because of some factors such as; delisted and there were no data about the companies, so there were only 59 companies that did an acquisition in 2002-2005, and Writer used these companies as objects in this research. The purpose of this research is to learn company's performance after acquisition. The Variable to see company's performance is firm size of total assets, equity and sales, and also growth of total assets, equity, and sales. Results of regression linear, shows acquisition it raises company's performance and effected equity and total assets. It doesn't affect sales aspect significantly, but it rose compared to the previous period. This happened because of some companies that have odd performance and are really different from other companies that conducted the acquisition. Because of limitation in doing this research, I want to give advice to the next research to learn this topic deeper and to see it more from macro economy perspective.